Case Writing And Analysis: Victor Company Of Japan Ltd - Cho, Nam Sang (2006)
The main theme of this case study is to review one of the Japanese consumer electronics companies namely Victor Company of Japan, also known as JVC in the overseas market, on how the company takes on the challenges of liberalization of global trade as well as the double challenges faced by the company, that is the convergence technology and the onslaught of the Chinese manufacturers.